Women breadwinners profile, level of marital and job satisfaction. - Magbanua, Therese Mary E.
Due to the women's movement there have been a growing number of women breadwinners. Therefore this study aims to describe and determine the profile, level of marital and job satisfaction of ten (10) self-employed and ten (10) emplyed breadwinners in Iloilo City, and investigate whether there is a relationship between the both. The Rouch Frazier Marital Satisfaction and Career Satisfaction Survey were utilized. The results showed that respondents have high levels of marital and job satisfaction with their career, and a direct and positive correlation between both. This maybe expected because most of the respondents worked within the city and had few children. They also had in-laws and household help to make balancing their life and jobs easier.